The involvement of transcriptional read-through from internal promoters in the expression of a novel endoglucanase gene FSendA, from Fibrobacter succinogenes AR1. - Cavicchioli, R (1991)
Two distinct mRNA transcripts were synthesized in Escherichia coli during expression of FSendA, an endoglucanase gene from Fibrobacter succinogenes AR1. Expression of FSendA required a ribosomal frameshift between open reading frame 1 (ORF1) and ORF2 to allow contiguous translation of a 453 amino acid protein (1). The primary transcript initiated upstream of ORF1 and the secondary transcript from within ORF1. Both transcripts terminated downstream of ORF2 and termination was essential for endoglucanase expression. Deletion of the primary transcript promoter region allowed read-through of the secondary transcript beyond the terminator region, indicating that a component of the intact FSendA gene allowed efficient transcription termination. The possibility of autogenous regulation by translation products is suggested.